Biochemical and genetic characterization of a yeast TFIID mutant that alters transcription in vivo and DNA binding in vitro. - Arndt, K M (1992)
A mutation in the gene that encodes Saccharomyces cerevisiae TFIID (SPT15), which was isolated in a selection for mutations that alter transcription in vivo, changes a single amino acid in a highly conserved region of the second direct repeat in TFIID. Among eight independent spt15 mutations, seven cause this same amino acid change, Leu-205 to Phe. The mutant TFIID protein (L205F) binds with greater affinity than that of wild-type TFIID to at least two nonconsensus TATA sites in vitro, showing that the mutant protein has altered DNA binding specificity. Site-directed mutations that change Leu-205 to five different amino acids cause five different phenotypes, demonstrating the importance of this amino acid in vivo. Virtually identical phenotypes were observed when the same amino acid changes were made at the analogous position, Leu-114, in the first repeat of TFIID. Analysis of these mutations and additional mutations in the most conserved regions of the repeats, in conjunction with our DNA binding results, suggests that these regions of the repeats play equivalent roles in TFIID function, possibly in TATA box recognition.